A novel diagnostic methodology for fuel cell stack health: Performance, consistency and uniformity. (1st April 2019) - Hu, Zunyan; Xu, Liangfei; Li, Jianqiu; Gan, Quanquan; Xu, Xin; Song, Ziyou; Shao, Yangbin; Ouyang, Minggao
Highlights: An in situ methodology has been proposed for fuel cell stack health diagnosis. Performance, consistency and uniformity decline have been considered in this methodology. This diagnostic methodology is easy to be conducted and validated by experiments. Abstract: Internal heterogeneity is a significant challenge to the service life of large-format commercial fuel cell stacks. Methods for diagnosing fuel cell stack health, however, are still lacking. This paper proposes a novel diagnostic methodology for analyzing the performance, the consistency between cells and the uniformity within individual cells of fuel cell stacks. Specifically, this three-step methodology can comprehensively analyze the internal heterogeneity of large-format multi-cell stacks. First, a polarization curve test is conducted to provide a quick qualitative performance analysis. Then, the quantitative parameters consistency decline is analyzed by galvanostatic charging and electrochemical impedance spectroscopy methods. Finally, a novel multi-point voltage monitoring method is applied to rule out possible misdiagnoses and to qualitatively analyze cell uniformity. This degradation diagnostic methodology is applied to analyze degradation in several fuel cell stacks, revealing high potential in practice.